PENGARUH REWARD AND PUNISHMENT, KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA GURU MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING PADA SMKN 1 KENDIT KABUPATEN SITUBONDO - Razak, Hadiesta Mahza Aliana; Praja, Yudha; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Organizations have various kinds of resources as input to be converted into output in the form of goods or services, human resources are also the most important element. The aim of this research is to analyze and test the influence of Reward and Punishment, Leadership and Work Discipline on Teacher Performance through Motivation as an Intervening Variable. The population used in this research were 35 teachers at SMKN 1 Kendit Situbondo. This sampling technique is saturated sampling. Data analysis and hypothesis testing in research uses Structural Equation Models - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that 1. Reward and punishment have a significant positive effect on work motivation. Leadership has a significant positive effect on work motivation. Work discipline has a significant positive effect on work motivation. Reward and punishment have a significant positive effect on performance. Leadership has a positive but not significant effect on performance. Work discipline has a positive but not significant effect on performance. Work motivation has a significant positive effect on performance. Then the results of the indirect influence hypothesis test show that the variable Reward and Punishment on Performance through Work Motivation has a positive but not significant effect. Leadership on Performance through work motivation has a significant positive effect. Work discipline on performance through work motivation has a significant positive effect